PENYULUHAN SADAR POTENSI DIRI MELALUI MEDIA TAYANGAN FILM EDUKASI (Jurnal Abdikarya: Jurnal Karya Pengabdian Dosen Dan Mahasiswa, 2019)
The main goal is to make children motivated to films that are good to watch and can be taken thelesson. The results achieved are the children are very enthusiastic because they gain new knowledgethrough the spectacle of this educational film. Follow-up is so that children can get used to watchinggood movies just like they have seen because of the lack of educational films available in the media.Keywords : Motivated, entushiastic, educational.